Penyuluhan Bahaya Cacingan bagi Siswa Sekolah Dasar Sebagai Upaya Mewujudkan Anak Indonesia Sehat dan Berprestasi - Shelviana Kirani Agustin; Adelia Ramadhani; Mitha Indah Herlina; Inggar Kinanti Imafluchah; Nadira Safira Darmaji Putri; Rizka Novia Atmadani (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to provide students with an understanding of Sumbersari 03 elementary students about the dangers of worms and how to prevent them. Most primary school students actively playing and unaware of how to care for themselves to be cleaner and healthier were exposed to intestinal worms. The method of implementing this service used counseling through PowerPoint media, brochures, and interactive videos. The instrument for evaluating this activity was a questionnaire in the form of a pretest and a post-test. The results of this service showed an increase in the understanding of grade 5 students at SDN Sumbersari 03 regarding worm infections and how to prevent them. In the pretest activities, 3 out of 24 students could only answer two questions correctly, while 3 out of 24 answered three questions correctly in the post-test activity. From these results, students' understanding was getting better. It is hoped that it will form a healthy and accomplished generation of Indonesian children.